Uji Mikrobiologi Serum Sarang Burung Walet (Collocalia fuciphaga) Sebagai Agen Aktif - Muhammad Tahir; Suhartini; Nur Zam Sabila (Jurnal Kesehatan Yamasi Makassar, 2026)
The demand for safe and effective natural cosmetic products is increasing, one of which is facial brightening serum. Swallow's nest (Collocalia fuciphaga) contains bioactive compounds such as glycoprotein and epidermal growth factor (EGF) which are known to have the potential as skin brightening agents. This study aims to test the effectiveness of facial serum containing swallow's nest extract from South Sulawesi in increasing skin brightness, and to compare it with Niacinamide-based serum. The study was conducted experimentally in the laboratory using 12 male white rats (Rattus norvegicus), which were divided into three treatment groups (concentrations of 10%, 20%, and 30%) and one positive control (Niacinamide). The back area of the rats was pigmented using UV-B and serum was applied for seven days. Brightness measurements were carried out using a skin tone scale. The results showed that serum with a concentration of 30% provided the most significant increase in brightness, with a decrease in skin tone value from 15 to 3, better than niacinamide.